9w-6=-7+9w

Simple and best practice solution for 9w-6=-7+9w equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9w-6=-7+9w equation:


Simplifying
9w + -6 = -7 + 9w

Reorder the terms:
-6 + 9w = -7 + 9w

Add '-9w' to each side of the equation.
-6 + 9w + -9w = -7 + 9w + -9w

Combine like terms: 9w + -9w = 0
-6 + 0 = -7 + 9w + -9w
-6 = -7 + 9w + -9w

Combine like terms: 9w + -9w = 0
-6 = -7 + 0
-6 = -7

Solving
-6 = -7

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 1-8k=-11k-23 | | 4(3w-3)-2(4w+7)= | | 0.136/8=d | | 2n+7n-5=2n-3n+10 | | 5v=5v-4 | | 4=0y+4 | | 5x-5b-5b= | | -5(-2w+5)-8w=6(w-2)-3 | | -7n+1=-7n+2 | | 0.5x-0.1(8-3x)=-0.6(x-8) | | 5.4a+11=70.4 | | 3x^2-200=-x^2-20 | | 2f+6f=8f | | -35=h-14 | | 0.4x-17.7=-2.5x+20 | | -3(7u-6)+6u=3(u+4) | | -8s=10-7s | | T^2+22t=-1 | | 3y+6=2y+12 | | 5g-7=28 | | Y=0.6(-5)+16 | | 31=-2y | | 10x+x=5460 | | 2x^3+6x^2+8x=-24 | | .7n=3.5 | | 20=6-x | | -94.72/37=x | | Log(9d+3)=log(3d-9) | | 23+b=10 | | -7x-5=-54 | | √9/25 | | Xxy=324 |

Equations solver categories